The role of nutritional factors in fat-free mass preservation and body composition changes after bariatric surgery: a systematic review of the available evidence - Behnaz Abiri; Majid Valizadeh; Zahra Seifi; Shirin Amini; Fatemeh Haidari (Eating and Weight Disorders)
Abstract Background Bariatric surgery (BS) is an effective treatment for obesity, but it often leads to significant changes in body composition, including loss of fat-free mass (FFM). Nutritional intake plays a crucial role in influencing these changes. This systematic review aims to assess the impact of nutritional strategies on body composition, specifically FFM preservation, following BS. Methods A systematic literature search was conducted across PubMed, Scopus, EMBASE, Web of Science, and Google Scholar using combinations of terms including ("bariatric surgery" OR "RYGB" OR "sleeve gastrectomy") AND ("nutritional intake" OR "dietary factors") AND ("lean body mass" OR "fat-free mass" OR "body composition"). We included studies examining adults who underwent bariatric surgery and reported quantitative relationships between postoperative nutritional intake (assessed through dietary records, recalls, or biomarkers) and changes in LBM/FFM. Data were extracted and synthesized to evaluate the effects of specific nutritional factors including protein quantity/quality, macronutrient distribution, and micronutrient status on body composition outcomes. Results Inadequate protein intake (< 60 g/day or < 1.2 g/kg ideal body weight) was common post-BS and associated with significant FFM loss (5–15% reduction). Higher protein intake (≥ 60 g/day or ≥ 1.2 g/kg) preserved FFM, particularly during the first 6 months, though results varied due to differences in study design and assessment methods. Macronutrient analysis revealed carbohydrate intake > 130 g/day correlated with poorer weight loss outcomes, while fat intake > 60 g/day was associated with greater FFM loss (2–4% additional reduction). Conversely, fiber intake > 25 g/day demonstrated protective effects. One trial of the Dietary Approaches to Stop Hypertension (DASH) diet demonstrated mixed body composition impacts. Conclusion Adequate protein intake is crucial for minimizing FFM loss after BS. Personalized nutrition plans, early counseling, and regular follow-ups are vital for improving long-term outcomes. However, variability in study results highlights the need for more research to develop standardized nutritional guidelines for post-surgery care.